Autoantibodies targeting interferons and GM-CSF are associated with adverse outcome risk, comorbidities, and pathogen in community-acquired pneumonia - Jakob Hjorth Von Stemann; Arnold Matovu Dungu; Maria Vispe Laguarda; Camilla Koch Ryrsø; Camilla Koch Ryrsø; Maria Hein Hegelund; Daniel Faurholt-Jepsen; Daniel Faurholt-Jepsen; Rikke Krogh-Madsen; Rikke Krogh-Madsen; Rikke Krogh-Madsen; Morten Bagge Hansen; et al. (Frontiers in Immunology, 2024)
IntroductionCytokine autoantibodies (c-aAb) have been associated with pulmonary diseases, including severe novel coronavirus disease 2019 (COVID-19) and pulmonary alveolar proteinosis. This study aimed to determine c-aAb association with community-acquired pneumonia (CAP) etiology (SARS-CoV-2, influenza, or bacteria) and c-aAb associations with CAP-related clinical outcomes and pulmonary comorbidities.MethodsIn a cohort of 665 patients hospitalized with CAP, c-aAb targeting interferon α (IFNα), IFNβ, IFNγ, interleukin-1α (IL-1α), IL-6, IL-10, and granulocyte-macrophage colony-stimulating factor (GM-CSF) were measured in plasma samples. Associations between c-aAb and baseline characteristics, pulmonary comorbidities, pathogen, intensive care unit (ICU) transferal, time to clinical stability, and mortality were estimated, with results stratified by sex.ResultsMore men infected with SARS-CoV-2 were had high-titer type 1 IFN c-aAb compared to other pathogens. Among patients with CAP, asthma and bronchiectasis comorbidities were associated with high-titer GM-CSF c-aAb in men, and men with high-titer IFNβ c-aAb had increased odds for ICU transferal. High-titer IL-10 c-aAb were associated with faster clinical stability in womenConclusionIn men with CAP, various c-aAb—including type 1 IFN and GM-CSF c-aAb—were associated with adverse clinical events and comorbidities, whereas c-aAb targeting an autoinflammatory cytokine were associated with a positive outcome in women. This suggests that the potentially immunomodulatory effects of c-aAb depend on pathogen, autoantibody specificity, comorbidity, and sex.